The effect of plant growth promoting rhizobacteria on germination and primary growth of Moldavian dragonhead (Dracocephalum moldavica L.) - V. Torfi; A. Danesh-Shahraki; K. Saeidi; M. Mobini-Dehkordi; P. Tahmasebi (علوم و فناوری بذر ایران)
In order to evaluation the effect of plant growth promoting rhizobacteria on germination and primary growth of Darcocephalum  moldavica L. an experiment in completely randomized design was conducted in the laboratory of agronomy science of Shahrekord University. Treatments were included control (no bacterial inoculation), inoculated with Rhodococcus sp., Corynebacterium sp., Mycobacterium sp., Bacillus sp., Azotobacter sp., Pseudomonas putida and Pseudomonas fluorescens bacteria and inoculated with a mixture of all bacteria. Results showed that a significantly effect of bacterial treatments on germination percentage, germination rate, mean germination time, germination rate index, half maximal activation level (T50), length and radical weight, shoot and seedling, vigor index and Allometric coecifficient at 1% probability level. Bacillus sp. bacterial inoculation treatment had the most influence on mean germination time, germination rate index, half maximal activation level (T50), length and radical weight, shoot and seedling, and vigor index traits. Bacteria incubation treatment of Rhodococcus sp. and Pseudomonasfluorescence hadthe most effect on germination speed and germination percentage, respectively. The results showed that bacterial inoculation treatments as biopriming can improve the germination and primary growth indices of D. moldavica herb.